A quantitative approach to cork oak forest management - Borges, JoséG; Oliveira, Ângelo C.; Costa, Maria a (Forest Ecology and Management, 1997)
Mathematical programming is one quantitative technique that can be used for strategic and tactical natural resources planning. It has been extensively used both at private and public forest planning levels. Nevertheless, most applications concentrate on modelling of systems involving timber harvesting. This paper focuses on cork oak (Quercus suber L.) forest management. It summarizes the methodology to follow in order to generate information needed for modelling purposes. It formulates a cork oak forest management problem using a linear programming model. A case study is used to illustrate the procedure used. The results of the research on a modelling approach to cork oak forest management for an area extending over 5272 ha in the Portuguese submediterranean ecological region are presented. Extensions to this study are identified.
Keywords: Forest regulation; Harvest scheduling; Linear programming; Mediterranean forestry; Quercus suber L.; Strategic planning